VLAN-reusing: A novel solution for efficient network virtualization. Issue 4 (1st October 2016) - Liu, Jiang; Huang, Tao; Xin, Yuanming; Zhang, Jiannan; Yu, F. Richard; Liu, Yunjie
Abstract: In network virtualization, slice isolation is a key issue since it is hard to realize in a distribute system in a flexible way. Recently, the rise of Software Defined Networking architecture provides a promising way to deal with this problem. Existing work leverage, and existing bits in the head field, such as VLAN ID, isolates the tenant traffic. However, we argue that more potential should be exploited in SDN architecture to isolate the network better. Following this consideration, we propose a new scheme called VLAN-Reusing. It enhances the isolation by reusing VLAN IDs with location information, while extending the VLAN quantity from 4096 to 4096*k (k refers to the number of links in the physical network) without changing the packet format. Simulation results show that the proposed scheme can shorten the latency between tenants and physical layers and enables greater capacity of tenants than traditional VLANs.